Factorise x^2-y^2-2x+6y-8
1 answer:
X^2 - y^2 - 2x + 6y - 8
<span>= (x^2 - 2x + 1) - (y^2 - 6y + 9) - 8 - 1 + 9 </span>
<span>= (x - 1)^2 - (y - 3)^2 </span>
<span>= [(x - 1) - (y - 3) ] [(x - 1) + (y - 3)] </span>
<span>= (x - 1 - y + 3) ( x - 1 + y - 3) </span>
<span>= (x - y + 2) (x + y - 4)</span>
You might be interested in
Hope this helps!!!!!!!!!!!!
Answer:
d
Step-by-step explanation:
Answer:
57/200 Km
Step-by-step explanation:
3/10*10= 30/100
30/100+27/100=57/200km
Answer:
41.74 and 41.89
Step-by-step explanation: